ChemInform Abstract: Organocatalytic Radical Involved Oxidative Cross‐Coupling of N‐Hydroxyphthalimide with Benzylic and Allylic Hydrocarbons. Issue 17 (April 2016) - Dian, Longyang; Wang, Sisi; Zhang‐Negrerie, Daisy; Du, Yunfei
Abstract: The cross‐coupling reaction between N‐hydroxyphthalimide and various benzylic and allylic hydrocarbons is realized through an organocatalytic radical‐mediated process involving C(sp 3 )—O bond formation using tert‐butyl hydroperoxide as an oxidant and tetra‐n‐butylammonium iodide as a catalyst, during which the phthalimide N‐oxyl radical and benzylic and allylic radicals are generated in situ and react selectively by a radical/radical cross‐coupling reaction.